Deprecjacja pieniądza—stopa procentowa—inflacja - Jankowiak, Ludwik (Wydział Prawa i Administracji UAM, 1975)
The author discusses in the paper the underlying causes for the present inflation in the capitalist world. He analyses at the beginning the permanent process of depreciation of currencies and the prevailing tendencies in banking rates. The causes of the inflation plague are complex. The author represents the opinion that the recent spasm of inflation has been touched off by two developments: 1) An extraordinary explosion in the price of commodities (comprising a wide range of goods), 2) The insistence of the world's nations — rich and poor alike — that they can increase consumption faster than production. The author next describes the different ways and means which are used to combat inflation, shows who are its main victims. The paper touches also on the internationalization of inflation processes (mainly through international trade) and finally analyses the signs of inflation processes which to a certain extent manifest themselves also in the socialist countries. The author points to the differences of inflationary processes in the capitalist and socialist systems.
Depreciation of Currencies — the Bank Rate — Inflation